Status, potential and improvement of Indian bean - Rai, Nagendra; Dubey, R. K.; Singh, Manish; Rai, K. K. (Indian Horticulture, 2020)
The genus Lablab refers to the hyacinth bean, bonavist bean, sem, egyptian bean, field bean, Australian pea, Indian butter bean and belongs to the family leguminosae (Fabaceae). In Flora Indica, Roxburgh (1832) exemplify ‘Dolichos’ in Dolichos lablab as Greek word that symbolize long pod and ‘lablab’ as Arabic or Egyptian word implying shallow vessel enclosing seed. Backer (1984) on the basis of shape, texture and angle of attachment of seeds to the suture of the pods categorized all the five cultivated varieties in two cross compatible botanical groups i.e., Lablab purpureus var. typicus and Lablab purpureus var. lignosus. Lablab purpureus L. var. typicus (Syn. Lablab niger var. typicus) is widely cultivated as garden type bean with soft pods that has long axis in which seeds are arranged parallelly to the suture and Lablab purpureus var. lignosus (Syn. Lablab niger var. lignosus) where the seeds are arranged at right angle to the suture, is mainly cultivated as field bean and most commonly used as pulse containing more protein (20.9-29.2%) than Lablab purpureus var. typicus.